Detecting language network alterations in mild cognitive impairment using task‐based fMRI and resting‐state fMRI: A comparative study - Kerem Kemik; Emel Ada; Berrin Çavuşoğlu; Cansu Aykaç; Derya Durusu Emek Savaş; Görsev Yener (Brain and Behavior, 2024)
Abstract Objective The objective of this study was to investigate the functional changes associated with mild cognitive impairment (MCI) using independent component analysis (ICA) with the word generation task functional magnetic resonance imaging (fMRI) and resting‐state fMRI. Methods In this study 17 patients with MCI and age and education‐matched 17 healthy individuals as control group are investigated. All participants underwent resting‐state fMRI and task‐based fMRI while performing the word generation task. ICA was used to identify the appropriate independent components (ICs) and their associated networks. The Dice Coefficient method was used to determine the relevance of the ICs to the networks of interest. Results IC‐14 was found relevant to language network in both resting‐state and task‐based fMRI, IC‐4 to visual, and IC‐28 to dorsal attention network (DAN) in word generation task‐based fMRI by Sorento‐Dice Coefficient. ICA showed increased activation in language network, which had a larger voxel size in resting‐state functional MRI than word generation task‐based fMRI in the bilateral lingual gyrus. Right temporo‐occipital fusiform cortex, right hippocampus, and right thalamus were also activated in the task‐based fMRI. Decreased activation was found in DAN and visual network MCI patients in word generation task‐based fMRI. Conclusion Task‐based fMRI and ICA are more sophisticated and reliable tools in evaluation cognitive impairments in language processing. Our findings support the neural mechanisms of the cognitive impairments in MCI.